A Detailed Analysis of Childhood Victimization Using National Registers: Forms and Sequencing of Violence and Domestic Abuse - Cédric Gorinas (Institute of Labor Economics (IZA), 2018)
Using highly detailed longitudinal data from Danish registers, this study overcomes limitations inherent in victimization surveys and compares the role of individual and family characteristics for five forms of childhood violence, including sexual assaults and threats. The study also examines repeated and poly-victimization and the factors underlying abuse by different types of domestic perpetrators. This study finds that children aged 0 to 12 are the most exposed to sexual abuse, aggravated violence, and domestic abuse; that 30% of young victims of sex and threats will be victimized again; and that the economic and physical vulnerability of the mother in particular is a strong risk factor for early abuse. This study shows the importance of national registers in uncovering under-researched areas of childhood victimization and identifying the most vulnerable groups.
Keywords: J12; J13; 330; victimization; domestic crime; violence; child abuse